A multi-center thai university-based surgical intensive care units study (THAI-SICU study): Outcome of ICU care and adverse events - Suneerat Kongsayreepong (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Surgical intensive care units (SICUs) are special units for critically ill surgical patients both in the pre and postoperative period. There is little aggregated information about surgical patients who are admitted to the Thai surgical ICU. The objective of this report was to describe patient characteristics, outcomes of ICU care, incidence and outcomes of adverse events in the SICU in the participating SICUs. Material and Method: This multi-center, prospective, observational study of nine university-based SICUs was done. All admitted patients with ages >18 years old were included. Information about patient characteristics, underlying medical problems, indication and type of ICU admission, severity score as ASA physical status in operative patients, APACHE II score and SOFA score, adverse events of interest, ventilator days, ICU and 28 days mortality. The association of outcome and predictors was reported by relative risk (RR) with 95% confidence interval (95% CI). Statistical significant difference was defined by p<0.05. Results: During April 2011-January 2013 of total cohort time, a total of 4,652 patients from nine university-based SICUs were included in this study. Mode of patient age was 71-75 year old for both sexes. Median (IQR) of APACHE II scores and SOFA scores were 10 (7-10) and 2 (1-5), respectively. Seventy eight percent of patients were postoperative patients and 50% of them were ASA physical status III. The median of ICU stay was 2 (IQR 1-4) days. Each day of ICU increment was associated with increased 1.4 days of a hospital stay. Three percent of survived at discharge were clinically inappropriate discharge resulting in ICU readmission. Sixty-five percent were discharged home after ICU admission. ICU and 28 days mortality was 9.6% and 13.8%. The seven most common adverse events were sepsis (19.5%), acute kidney injury (AKI) (16.9%), new cardiac arrhythmias (6.2%), acute respiratory distress syndrome (ARDS) (5.8%), cardiac arrest (4.9%), delirium (3.5%) and reintubation within 72 hours (3.0%), respectively. Most of the adverse events occurred in the first five days, significantly less occurred after 15 days of ICU admission. The association between adverse events and 28 days mortality were significant for cardiac arrest (RR, 9.5; 95% CI, 8.6-10.4), respiratory failure [acute respiratory distress syndrome (ARDS) (RR, 4.6; 95% CI, 3.9-5.3), acute lung injury (ALI) (RR, 2.7; 95% CI, 2.1-3.6)], acute kidney injury (AKI) (RR, 4.2; 95% CI, 3.7-4.8), sepsis (RR, 3.6; 95% CI, 3.2-4.2), iatrogenic pneumothorax (RR, 3.2; 95% CI, 2.1-5.1), new seizure (RR, 3.1, 95% CI, 2.2-4.4), upper GI hemorrhage (RR, 3.0, 95% CI, 2.1-4.1), new cardiac arrhythmias (RR, 2.9; 95% CI, 2.4-3.5), delirium (RR, 2.1; 95% CI, 1.7-2.8), acute myocardial infarction (RR, 2.1; 95% CI, 1.4-3.1), unplanned extubation (RR, 2.1; 95% CI, 1.4-3.1), intra-abdominal hypertension (RR, 1.8; 95% CI, 1.2-2.7) and reintubation within 72 hours (RR, 1.5; 95% CI, 1.1-2.1). Conclusion: This is the first large study of surgical critical care in Thailand, which had a systematic patient follow-up program. Most of the patients were elderly. Adverse events were most frequent during the first 5 days of admission and were associated with ICU and 28 days mortality.